2017
DOI: 10.1074/jbc.m117.803809
|View full text |Cite
|
Sign up to set email alerts
|

Ectodysplasin A protein promotes corneal epithelial cell proliferation

Abstract: The gene encodes ectodysplasin A (Eda), which if mutated causes X-linked hypohidrotic ectodermal dysplasia (XLHED) disease in humans. Ocular surface changes occur in XLHED patients whereas its underlying mechanism remains elusive. In this study, we found Eda was highly expressed in meibomian glands, and it was detected in human tears but not serum. Corneal epithelial integrity was defective and the thickness was reduced in the early postnatal stage of mutant mice. Corneal epithelial cell proliferation decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 32 publications
(30 reference statements)
4
28
0
Order By: Relevance
“…Previous studies reported decreased cell proliferation in Eda −/− corneas, along with impaired wound healing (Li et al, 2017). As our results indicate a misregulation of the growth factors produced by the LG, we hypothesized a defective response of Eda −/− LG to corneal insult, resulting in an impaired wound healing process.…”
Section: Eda Loss Of Function Results In Impaired Lg Maturationsupporting
confidence: 52%
See 4 more Smart Citations
“…Previous studies reported decreased cell proliferation in Eda −/− corneas, along with impaired wound healing (Li et al, 2017). As our results indicate a misregulation of the growth factors produced by the LG, we hypothesized a defective response of Eda −/− LG to corneal insult, resulting in an impaired wound healing process.…”
Section: Eda Loss Of Function Results In Impaired Lg Maturationsupporting
confidence: 52%
“…Previous work suggested a modulation of tear film composition when reflex tears are produced, to support corneal wound healing (for a review, see Klenkler et al, 2007), and Eda −/− animals were recently shown to have a slower corneal epithelium wound healing (Li et al, 2017). Here, we showed that Cxcl10, Hgf, Fgf7 and Tgfb1, all involved in corneal wound healing (Tervo et al, 1997;Tuominen et al, 2001;Wilson et al, 1999), were misregulated in Eda −/− LGs.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations